Design a photovoltaic simulator system based on two-diode model with linear interpolation method - Lam Quang Thai; An Thi Hoai Thu Anh (Institute of Advanced Engineering and Science, 2022)
For an effective study of photovoltaic (PV) systems, precise current-voltage (I-V), power – voltage (P-V) curves of photovoltaic modules are required. However, conducting experiment on real panels faces with many difficulties such as needing large space, high cost, objective conditions of the environment. Therefore, it is essential to research an emulator producing the I-V, P-V characteristics of a PV system the same as those conducted on a real PV panel. This paper presents a two–diode model simulation replacing a photovoltaic panel to export precise current-voltage (I-V), power – voltage (P-V) curves based on the linear interpolation method. The proposed simulator shows many advantages of subjecting to changes in radiation and temperature. The accuracy of the emulator has been not only verified by the simulation results on Matlab software, but also evaluated, compared with the experiment model. The simulation results have coincided with the experimental ones, the output error of less than 4% is shown in the experiment.